Measuring the Acceleration of a Rigid Body - Peter G. Martin; Gregory W. Hall; Jeff R. Crandall; Walter D. Pilkey (Shock and Vibration)
Two methods to measure the six-degree-of-freedom acceleration of a point on a rigid body are presented. The first, referred to as the periphery scheme, makes use of three clusters of accelerometers mounted orthogonal to each other and coincident with the axes of the point. One of the clusters consists of the three accelerometers attached to a cube-shaped triaxial angular rate sensor (ARS). The second method, called the compact cube scheme, uses a single 3-accelerometer/ARS cluster that may be mounted anywhere on the rigid body. During impact tests with an instrumented rigid body, both methods produced measurements that were highly correlated near the time of peak acceleration. Whereas the compact cube scheme was more economical and easier to implement, the periphery scheme produced results that were less disrupted by instrument signal errors and noisy environments.